Female Genital Cutting Restricts Sociosexuality Among the Igbo People of Southeast Nigeria. (6th May 2016) - Onyishi, Ike E.; Prokop, Pavol; Okafor, Chiedozie O.; Pham, Michael N.
Female genital cutting (FGC) involves partial or total removal of the external female genitalia and causes detrimental effects on woman's physical and psychological health. Estimates suggest that 130 million women and girls have experienced FGC worldwide. A frequently cited reason for performing this procedure is to restrict female sexuality. To test this idea, we examined women's willingness to engage in uncommitted sexual relations (sociosexuality) among the traditional Igbo community in Southeastern Nigeria, a region in which FGC is prevalent. Women with FGC reported more restricted sociosexuality in all three domains (attitude, behavior, and desire) compared to women without FGC. Our results suggest that FGC significantly restricts female extra-pair behavior. We provide evidence that this practice is partially attributable to sexual conflict over reproduction by decreasing paternity uncertainty and increasing the reproductive costs to women.